Benefits of active life in student experiences during COVID-19 pandemic time - Pišot, Saša; Milovanović, Ivana M.; Katović, Darko; Bartoluci, Sunčica; Radenović, Sandra S. (Frontiers in Public Health, 2022)
The first wave of the COVID-19 pandemic has led to extreme global consequences. In this paper, changes in the basic segments of students’ everyday life and their subjective perception are investigated. The research was conducted in Croatia, Serbia and Slovenia. The application of the mixed method was performed to provide breadth and depth of understanding of students’ responses to lifestyle changes. The research was conducted in two phases: a quantitative, using an online survey (N = 1055), from April 15th to April 28th 2020, and a qualitative, using semi-structured interviews (N = 30), from June 10th to July 27th 2020. Students showed similar responses to the measures, but it turned out that the response in that population was different when their gender and study program were taken into account as well as the duration of the restrictive measures. The results suggest that students of study programs that are not "health-related" were more sensitive to change in habits than students of “health-related” study programs, but generally changes are visible in sleep patterns (going to bed late and waking up 60 to 80 minutes earlier). At the same time, the time spent in front of screens increased, from M = 4.49 (SD = 2.72) hours to M during Covid-19 = 8.27 (SD = 3.44) hours, not only due to the transition to e-learning, but also due to a “stay at home” measure. Furthermore, students were less physically active, there was a decrease in exercise by 20 minutes (SD = 86.52) and a decrease in walking (mean = 54 minutes, SD = 103.62) per day, and what is positive is that they were able to maintain the recommended amount of physical activity. The research contributes to the understanding of the social consequences of extraordinary measures in students as young, healthy and highly educated social actors, as well as a deeper insight into everyday strategies they undertake to counter or adapt to the “new normal” and the need for students to know the positive benefits of a healthy lifestyle.